Clinical pharmacogenetics of ibuprofen enantiomers after lower third molar surgeries - Weckwerth, Giovana Maria (2020)
Non-steroidal anti-inflammatory drugs (NSAIDs) are over-the-counter agents frequently consumed by the population in order to control chronic pain and also acute pain after inflammatory processes. Extraction of lower third molars is recommended for evaluation of the NSAIDs effect since it generates pain, swelling and trismus. Metabolism of NSAIDs is mainly dependent on the family of cytochrome P450 (CYP), more precisely CYP2C8 and CYP2C9 genes. In this context, pharmacogenetics, which studies the contribution of polymorphisms and genetic factors to the individual variability of responses to drug metabolism, is growing and starting to show results regarding the clinical use of drugs. In addition, the possible influence of genetic and tissue biomarkers at the descending inhibitory system of pain, may also impact the response and effects of NSAIDS, and this inhibitory system could be checked through the modulation of conditioned pain. In this aspect, the OPRM1 opioid receptor has been widely studied by pharmacogenetics, due to the structural variation, and its function in a variety of painful disorders. The -opioid receptor (MOR), encoded by the OPRM1 gene naturally regulates the analgesic response to pain. Genetic variabilities in the OPRM1 gene, particularly A118G SNP have been associated with a number of functional purposes. Thus, the aim of this study was assess the link between the different haplotypes of CYP2C8, CYP2C9 CYP1A2, CYP3A4 and CYP3A5 genes and the clinical efficacy of ibuprofen after lower third molar extractions regarding pain, swelling and trismus, adverse reactions, the amount of pain medication used, the patients satisfaction with the drug and the influence of the ability on preoperative modulation of conditioned pain. The relationship between the different haplotypes of the OPRM1 and COMT gene was also evaluated, the salivary concentrations of the pro-inflammatory cytokines (IL-2, IL-6, IFN-g and TNF-), and the modulation of pre- operative. The genetic sequencing of 200 Brazilian patients was carried out, with genomic DNA extracted from their saliva, from the genes CYP2C8, CYP2C9 CYP1A2, CYP3A4, CYP3A5, OPRM1 and COMT, using MiSeq® System (Illumina®) instruments with a 2 x 78bp read length, to check for possible new correlations of these genes with postoperative pain and modulation of pain, at Kailos Genetics, Inc. in Huntsville, Alabama, United States of America.